2019
DOI: 10.1021/acssuschemeng.9b03963
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Copper Iodide Cluster-Based Pellet Sensor for Highly Selective Optical Detection of o-Nitrophenol and Tetracycline Hydrochloride in Aqueous Solution

Abstract: o-Nitrophenol (o-NP) and tetracycline hydrochloride (TCH) residues in various aquatic environments are two environmental contaminants, which are seriously dangerous to both social safety and the environment. Detection of such species in a water system with one optical sensor is coveted for outdoor operation but has not been reported. Herein, we report the function synergistic strategy for the construction of a stable and luminescent hybrid copper­(I) iodine cluster-based sensor [Cu4I4(ETBT)4] (UJN-Cu2, ETBT = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 65 publications
(86 reference statements)
0
18
0
Order By: Relevance
“…Tetracyclines (TCs), including tetracycline (TET), oxytetracycline (OXY), and doxycycline (DOX), have been extensively employed for the prevention and control of microorganic infections because of the broad-spectrum antibacterial effect, availability, and low cost. However, the overdose or long-term low dose use of TCs can lead to residues in animal products, which would cause direct toxicity, liver damage, allergic action, and bacterial resistance . In order to ensure food security and protect consumer health, several countries have defined the maximum residue limits (MRLs) for TCs residues in animal-based foods.…”
Section: Introductionmentioning
confidence: 99%
“…Tetracyclines (TCs), including tetracycline (TET), oxytetracycline (OXY), and doxycycline (DOX), have been extensively employed for the prevention and control of microorganic infections because of the broad-spectrum antibacterial effect, availability, and low cost. However, the overdose or long-term low dose use of TCs can lead to residues in animal products, which would cause direct toxicity, liver damage, allergic action, and bacterial resistance . In order to ensure food security and protect consumer health, several countries have defined the maximum residue limits (MRLs) for TCs residues in animal-based foods.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the fluorescence lifetime of the complexes has almost no change before and after quenching, which indicates that the fluorescence quenching phenomenon is mainly caused by the static quenching effect mechanism. 78 …”
Section: Resultsmentioning
confidence: 99%
“…6a). 85 The lifetime of NJU-Cu2 centred at the emission peak of 578 nm was ∼6.21 μs. This strong emission is ascribed to the charge transfer triplet excited state between Cu and the ligand, which is consistent with previous relevant mechanism studies of the copper iodine cluster.…”
Section: Copper Iodide Cluster-based Lmofsmentioning
confidence: 97%
“…83 Recently, two Cu x I y -based LMOFs have been reported as luminescence sensors for monitoring antibiotics. 84,85 In 2018, G. Liu et al synthesized a novel chair-like [Cu 4 I 4 ] cluster-based LMOF, [Cu 4 I 4 (EBT) 5 ] (UJN-Cu, EBT = 3-ethyl-1,3benzothiazole-2-thione) (Fig. 5a).…”
Section: Copper Iodide Cluster-based Lmofsmentioning
confidence: 99%